Haar wavelet method for constrained nonlinear optimal control problems with application to production inventory model - Waleeda Swaidan,; Amran Hussin, (Universiti Kebangsaan Malaysia, 2016)
A new numerical method was proposed in this paper to address the nonlinear quadratic optimal control problems, with state and control inequality constraints. This method used the quasilinearization technique and Haar wavelet operational matrix to convert the nonlinear optimal control problem into a sequence of quadratic programming problems. The inequality constraints for trajectory variables were transformed into quadratic programming constraints using the Haar wavelet collocation method. The proposed method was applied to optimize the control of the multi-item inventory model with linear demand rates. By enhancing the resolution of the Haar wavelet, we can improve the accuracy of the states, controls and cost. Simulation results were also compared with other researchers’ work.